Comparison of Pinoresinol and its Diglucoside on their ADME Properties and Vasorelaxant Effects on Phenylephrine-Induced Model - Pu, Yiqiong; Cai, Yiqing; Zhang, Qi; Hou, Tianling; Zhang, Teng; Zhang, Tong; Wang, Bing (Frontiers in Pharmacology, 2021)
Pinoresinol (PINL) and pinoresinol diglucoside (PDG), two natural lignans found in Eucommia ulmoides Oliv. (Duzhong), have several pharmacological activities. However, there is no report available on their absorption, distribution, metabolism, and elimination (ADME) properties. Given the possible wide spectrum of their application in therapeutic areas, this area should be investigated. This work studied the in vitro ADME properties of PDG and PINL, including their kinetic solubility, permeability across monolayer cells (PAMPA), protein binding, and metabolic stabilities in liver microsomes. The in vivo pharmacokinetic study and in vitro vasorelaxant effects on isolated phenylephrine-induced aortic rings of PINL and PDG were also investigated. It was found that both of their kinetic solubility in PBS (pH 7.4) was greater than 100 µM, indicating that they are both soluble compounds. The permeability investigations (Peff ) by PAMPA indicated that PINL had higher permeability than PDG (P <0.05). Both components represented moderate plasma protein binding activities (average binding rate in human plasma: PINL 89.03%, PDG 45.21%) and low metabolic rate (t1/2 in human liver microsome: PINL 1509.5 min, PDG 1004.8 min). Furthermore, the results of pharmacokinetic studies indicated that PINL might be eliminated less quickly than PDG from the rat plasma, and its cumulative urinary excretion was much lower than that of PDG. The phenylephrine-induced aortic rings demonstrated concentration-dependent vasorelaxation in PDG, PINL, or their combination group. The vasorelaxant effects of PINL were more obvious than those of PDG, whereas the vasorelaxant effect of the combinations was significantly better than that of the single component (P <0.05). The similarity or difference between PINL and its diglucoside in these pharmaceutical aspects may offer valuable insights into the further exploration of lignans and might contribute to relevant studies involving natural products with similar molecular structure and their glucosides.